2014
DOI: 10.1074/jbc.c114.601088
|View full text |Cite
|
Sign up to set email alerts
|

The Rpb4/7 Module of RNA Polymerase II Is Required for Carbon Catabolite Repressor Protein 4-Negative on TATA (Ccr4-Not) Complex to Promote Elongation

Abstract: Background: mRNA transcription and decay are coordinated processes. Results: The Rpb4/7 module of RNA polymerase II is required for the transcription and mRNA decay factor Ccr4-Not to associate with elongation complexes. Conclusion: Association between these two entities is required for Ccr4-Not to promote transcription elongation. Significance: Our work provides molecular insights into how transcription and mRNA decay are linked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 26 publications
5
51
0
Order By: Relevance
“…At this point, we propose that Asr1 ubiquitylates Rpb1-and likely other factors-the result of which is ejection of the Rpb4/7 heterodimer and termination of subtelomeric transcription. Although Rpb4/7 are dispensable for transcriptional elongation in vitro (6), this model is compatible with our observation that Asr1-associated pol II is catalytically inactive (5) and that transcriptional elongation by pol II in vivo can be stimulated by Rpb4/7 (17)(18)(19). After transcription is terminated, we suggest that corecruitment of Ubp3 with Asr1 allows rapid reversal of Rpb1 ubiquitylation, reassembly of the pol II complex, and restoration of polymerase function.…”
Section: Discussionsupporting
confidence: 87%
“…At this point, we propose that Asr1 ubiquitylates Rpb1-and likely other factors-the result of which is ejection of the Rpb4/7 heterodimer and termination of subtelomeric transcription. Although Rpb4/7 are dispensable for transcriptional elongation in vitro (6), this model is compatible with our observation that Asr1-associated pol II is catalytically inactive (5) and that transcriptional elongation by pol II in vivo can be stimulated by Rpb4/7 (17)(18)(19). After transcription is terminated, we suggest that corecruitment of Ubp3 with Asr1 allows rapid reversal of Rpb1 ubiquitylation, reassembly of the pol II complex, and restoration of polymerase function.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, the sensitivity of the transcript to single-stranded specific RNase indicates that extended RNA-DNA hybrids were not formed on the vast majority of the templates. All of the data described here, and elsewhere (28,(43)(44)(45)(46), indicate that this template produces ECs with the expected nucleic acid scaffold.…”
Section: Characterization Of Elongation Complexes Formed From Endinitmentioning
confidence: 99%
“…Templates-We use a minimal system for assembling ECs from highly purified components (28,(43)(44)(45)(46). RNAPII elongation was initiated from a 3Ј single strand extension on a duplex template to assemble an EC with a defined transcript produced from a G-less cassette (Fig.…”
Section: Characterization Of Elongation Complexes Formed From Endinitmentioning
confidence: 99%
“…The Ccr4-Not complex was purified from 16-liter cultures of yeast containing a tandem affinity purification (TAP)-tagged version of CAF40 and a deletion of DST1, as described in previous publications (24,25). The purified complex was dialyzed in dialysis buffer (20 mM HEPES, pH 7.6, 150 mM KCl, 10% glycerol), followed by concentration using a microfiltration device.…”
Section: Methodsmentioning
confidence: 99%
“…Though the possibility that it has the ability to affect the elongation stage of transcription has been suggested by genetic studies (23), only recently have biochemical analysis confirmed that it plays a direct role in stimulating transcription elongation (22,24). The Ccr4-Not complex binds to elongation complexes (ECs) by directly interacting with both the Rpb4/Rpb7 module of RNAPII and the emerging transcript (25). Once it is bound to arrested ECs, it reactivates backtracked RNAPII, which apparently does not involve transcript cleavage.…”
mentioning
confidence: 99%